Upaya Hukum Penyelesaian Sengketa Hak Asuh Anak Pasca Perceraian dalam Perspektif Hukum Perdata dan Kompilasi Hukum Islam: Studi Putusan Nomor 291 K/Ag/2024 - Amira Adila; Hasim Purba; Rosnidar Sembiring (Jurnal Hukum Lex Generalis, 2026)
Disputes over child custody which frequently give rise to conflicts, particularly during the enforcement stage of court decisions. The research focuses on parental legal responsibility, legal protection of children and dispute resolution mechanisms from the perspectives of Civil Law and the Compilation of Islamic Law. This study employs a normative juridical method using statutory and case approaches, with secondary data analyzed qualitatively. The findings indicate that the principle of the best interests of the child constitutes the primary basis for determining custody. Legal protection encompasses the fulfillment of children’s rights to education, welfare and safety. The harmonization of Civil Law and the Compilation of Islamic Law is essential to ensure comprehensive and sustainable protection of children’s rights.